The theological significance of the propeht Huldah's prophecy : a feminist perspective on 2 Kings 22:14-20 - Adonis, Melany Marildia (Stellenbosch : Stellenbosch University, 2012)
Thesis (MTh)--Stellenbosch University, 2002.